Correlation and regression analysis of the KRT27 and ELOVL4 genes in cashmere fineness and other production performances in Liaoning cashmere goats - H. Ma; W. Hong; L. Nie; S. Li; Q. Yuan; R. Duan; Q. Zhan; L. Kong; Z. Wang (Archives Animal Breeding)
This research aims to explore how polymorphism in the keratin 27 (KRT27) and ELOVL fatty acid elongase 4 (ELOVL4) genes relates to the production traits of Liaoning cashmere goats (LCGs). PCR-seq was used to detect gene polymorphism in the experimental population DNA, and its correlations with production performance and regression analysis were calculated using the SPSS software. Single-nucleotide polymorphism (SNP) at locus 1919G/A was identified within KRT27, and the GG genotype showed superior wool fineness in doe, whereas the GA genotype showed favorable traits in buck. A SNP at locus 28666C/T was identified within ELOVL4, and the CC genotype showed excellent performance for cashmere fineness. The multi-genic effect genotype that affects the fineness of cashmere is a GGTT haplotype combination. Through multiple linear regression (MLR) analysis, it was found that the trait with the greatest direct impact on cashmere production performance and fineness is the cashmere yield rate, with a correlation coefficient of 0.915. The type with the greatest direct impact on lactation performance and cashmere fineness is TS, with a correlation coefficient of 16.369. The pleiotropism genotype that affects the fineness and related traits of cashmere has been determined to be the TT type. The GGTT haplotype combination, as an advantageous genotype that simultaneously affects cashmere fineness and lactation performance, can serve as a molecular marker of cashmere-fineness-assisted selection and provide a theoretical basis for the selection, breeding, and expansion of new fine-fiber strains of LCGs.